2021
DOI: 10.1007/s00345-021-03810-6
|View full text |Cite
|
Sign up to set email alerts
|

Association between SARS-CoV-2 infection and disease severity among prostate cancer patients on androgen deprivation therapy: a systematic review and meta-analysis

Abstract: Purpose Androgen-regulated enzymes such as the angiotensin-converting enzyme 2 (ACE2) and the transmembrane serine protease 2 (TMPRSS2) are involved in the SARS-CoV-2 infection process. The expression of TMPRSS2 and its fusion gene, which are increased in the epithelium of the human prostate gland during prostate carcinogenesis, are regulated by androgens. Our goal was to assess the risk of the SARS-CoV-2 infection and the severity of the disease in PCa patients treated with androgen deprivation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…[40] Many systematic reviews and meta-analysis have delineated ACE2 and TMPRSS2 genes to increase the risk of susceptibility and severity of COVID-19. [41][42][43] This could lead to tubulopathy or even renal failure, which could explain the loss of free water or sodium retention for hypernatremia. However, ICU patients are at high risk of hypernatremia due to their inability to maintain free water balance due to sedation, intubation and fluid restrictions for various other reasons.…”
Section: Discussionmentioning
confidence: 99%
“…[40] Many systematic reviews and meta-analysis have delineated ACE2 and TMPRSS2 genes to increase the risk of susceptibility and severity of COVID-19. [41][42][43] This could lead to tubulopathy or even renal failure, which could explain the loss of free water or sodium retention for hypernatremia. However, ICU patients are at high risk of hypernatremia due to their inability to maintain free water balance due to sedation, intubation and fluid restrictions for various other reasons.…”
Section: Discussionmentioning
confidence: 99%
“…The immunological imbalance complicated by the testosterone blockade could represent an additional significant risk factor for a severe-to-critical disease in these subjects since the treatment reduces the androgen signaling and, likely, its anti-inflammatory function. While the literature data show that androgen deprivation therapy does not modify the risk of the infection itself [ 31 ], data on its influence on the prognosis are controversial. In fact, a recent trial failed to detect significant differences between those subjects undergoing anti-androgenic treatment and the controls [ 32 ], and a metanalysis of the available data could only show a trend of risk reduction [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is a theoretical role for ADT in the prevention of serious complications from COVID-19 as the transmembrane serine protease 2 is said to facilitate Severe acute respiratory syndrome coronavirus 2 cellular entry and is regulated by androgens [39]. However, multiple systematic reviews have found no association between ADT and reduced COVID-19 infection or mortality [40][41][42], suggesting no protective role of ADT for PCa patients against COVID-19. The use of ADT, although, could be beneficial when postponement of curative treatment for localised PCa is anticipated.…”
Section: Intermediate-risk Patientsmentioning
confidence: 99%